Modeling the Laws of Airborne Distribution of Dust Particles Generated in Primary Cotton Processing Plants - Sharibayev Nosir Yusubjanovich; Tursunov Ahror Aminjon o’g’li; Djurayev Sherzod Sobirjonovich (Genius Journals, 2022)
In this article was given ideas on mathematical modeling of the laws of airborne distribution of dust particles generated in primary cotton processing plants, the laws of airborne distribution of various chemically harmful dust particles, as well as the physical variables of the air environment views on the modeling of dust particle dispersion processes in the working zone, such as stability, air flow rate, numerical values of indicators
Keywords: Chemical contaminants; dust; working zone; dust particles; particle size; distribution laws; modeling